Toner and toner manufacturing method
The toner, featuring porous toner base particles with a specific size range and surface area, addresses the challenges of low-temperature fixing and heat-resistant storage, achieving superior performance in both aspects.
Patent Information
- Application Number
- JP2023161472
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-07
AI Technical Summary
Existing toners face challenges in achieving both low-temperature fixing properties and heat-resistant storage properties, as described in Patent Document 1.
The toner comprises toner particles with a porous structure, specifically toner base particles containing a polyester resin binder, a medium volume diameter of 6.0 μm to 8.0 μm, and a BET specific surface area of 1.1 m²/g to 1.4 m²/g, which are produced through a method involving hydrolysis of polyester resin on toner raw material particles.
This toner solution provides excellent low-temperature fixing properties and heat-resistant storage properties by optimizing the porous structure and size of the toner base particles, ensuring efficient heat transfer during fixing and preventing particle aggregation during storage.
Smart Images

Figure 2025052655000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner and a method for producing a toner. [Background technology]
[0002] In image formation by electrophotography, a toner containing toner particles is used. The toner is required to have low-temperature fixing property and heat-resistant storage property. In response to such requirements, for example, a capsule toner has been proposed that is composed of at least toner base particles containing a binder resin, a colorant, and a release agent, a coating layer that coats the surface of the toner base particles, and an external additive that is externally added to the surface of the coating layer (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-145063 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the present inventors have found through their investigations that it is difficult to reliably achieve satisfactory low-temperature fixability and heat-resistant storage stability even with the toner described in Patent Document 1.
[0005] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a toner having excellent low-temperature fixing property and heat-resistant storage stability. [Means for solving the problem]
[0006] The toner according to the present invention includes toner particles. The toner particles include toner base particles. The toner base particles contain a binder resin. The binder resin contains a polyester resin. The toner base particles have a porous structure. The toner base particles have a volume median diameter of 6.0 μm or more and 8.0 μm or less. The toner base particles have a BET specific surface area of 1.1 m2 / g or more 1.4m 2 / g or less.
[0007] The toner manufacturing method according to the present invention is the above-mentioned toner manufacturing method, and includes a dispersion liquid preparation step of preparing a dispersion liquid containing toner raw material particles, and a porosity forming step of obtaining the toner mother particles by forming the porous structure in the toner raw material particles. The toner raw material particles contain the polyester resin. In the porosity forming step, the dispersion liquid is treated with a base to hydrolyze a part of the polyester resin present on the surface of the toner raw material particles. Effect of the Invention
[0008] The toner and the method for producing the toner according to the present invention can provide a toner having excellent low-temperature fixability and heat-resistant storage stability. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view illustrating an example of a toner particle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A preferred embodiment of the present invention will be described below. The toner is an aggregate (e.g., powder) of toner particles. The external additive is an aggregate (e.g., powder) of external additive particles. Unless otherwise specified, the evaluation results (values indicating shape, physical properties, etc.) of the powder (more specifically, the powder of toner particles, the powder of external additive particles, etc.) are the number averages of values measured for each of a considerable number of particles selected from the powder.
[0011] Volume median diameter of powder (D 50 ) unless otherwise specified, is a value measured based on the Coulter principle (pore electrical resistance method) using a particle size distribution measuring device (e.g., Coulter Counter Multisizer 3 manufactured by Beckman Coulter, Inc.).
[0012] Unless otherwise specified, the number average primary particle diameter of a powder is the number average value of the circle equivalent diameters of primary particles (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) measured using a scanning electron microscope. The number average primary particle diameter of a powder is, for example, the number average value of the circle equivalent diameters of 100 primary particles. The number average primary particle diameter of particles refers to the number average primary particle diameter of particles in the powder unless otherwise specified.
[0013] Unless otherwise specified, the chargeability refers to the chargeability in triboelectric charging. For example, a standard carrier (standard carrier for negatively charged toner: N-01, standard carrier for positively charged toner: P-01) provided by the Imaging Society of Japan is mixed with the measurement target (e.g., toner) and stirred to triboelectrically charge the measurement target. The charge amount of the measurement target is measured before and after triboelectric charging, for example, with a small suction-type charge amount measuring device (Trek's "MODEL 212HS"), and the greater the change in charge amount before and after triboelectric charging, the stronger the chargeability of the measurement target.
[0014] Unless otherwise specified, the "major component" of a material means the component that is contained in the largest amount in the material on a mass basis.
[0015] Unless otherwise specified, the acid value is a value measured in accordance with "JIS (Japanese Industrial Standards) K0070-1992".
[0016] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the compound name is followed by "based" to represent the name of a polymer, it means that the repeating unit of the polymer is derived from the compound or its derivative. Acrylic and methacrylic may be collectively referred to as "(meth)acrylic".
[0017] <First embodiment: Toner> A first embodiment of the present invention relates to a toner. The toner of this embodiment includes toner particles. The toner particles include toner base particles. The toner base particles contain a binder resin. The binder resin includes a polyester resin. The toner base particles have a porous structure. The volume median diameter of the toner base particles is 6.0 μm or more and 8.0 μm or less. The BET specific surface area of the toner base particles is 1.1 m 2 / g or more 1.4m 2 / g or less. Note that, "the toner base particles have a porous structure" means that, for example, when the surface of the toner base particles is observed with an electron microscope, a porous structure consisting of nano-level pores is observed. It is preferable that the toner particles further include an external additive that adheres to the surface of the toner base particles.
[0018] The toner of the present embodiment can be used, for example, as a positively charged toner for developing an electrostatic latent image. The toner of the present embodiment may be used as a one-component developer. The toner of the present embodiment may be mixed with a carrier using a mixing device (for example, a bowl mill) and used as a two-component developer. When used as a one-component developer, the toner of the present embodiment is, for example, positively charged by friction with a developing sleeve or a toner charging member in a developing device. An example of a toner charging member is a doctor blade. When used as a two-component developer, the toner of the present embodiment is, for example, positively charged by friction with a carrier in a developing device. Details of the toner will be described below with reference to the drawings as appropriate.
[0019] Fig. 1 shows an example of a toner particle 1 contained in a toner. The toner particle 1 shown in Fig. 1 includes a toner base particle 2 and an external additive 3 attached to the surface of the toner base particle 2. A plurality of pores P are formed on the surface of the toner base particle 2. In other words, the toner base particle 2 has a porous structure.
[0020] The toner particles have been described above with reference to the drawings. However, the toner particles included in the toner of this embodiment may have a structure different from that of the toner particle 1 shown in FIG. 1. Specifically, the toner particles may contain particles other than silica particles as an external additive (hereinafter, may be referred to as "other external additive particles"). The toner particles may not contain an external additive. Furthermore, the toner mother particles may be capsule toner particles including a toner core and a shell layer that covers the toner core.
[0021] The toner of the present embodiment has the above-mentioned configuration, and therefore has excellent low-temperature fixing property and heat-resistant storage stability. The reason for this is explained below. The toner base particles of the toner of the present embodiment have a porous structure, and therefore the BET specific surface area is appropriately increased (BET specific surface area is 1.1 m). 2 / g or more 1.4m 2 / g or less). The toner base particles of the toner of the present embodiment have an appropriate size (volume median diameter is 6.0 μm or more and 8.0 μm or less). The toner base particles of the toner of the present embodiment have an appropriately large BET specific surface area and an appropriate volume median diameter, so that the entire toner image on the recording medium can efficiently receive heat from the fixing device during fixing. As a result, the toner of the present embodiment can be fixed even at a relatively low temperature, and has excellent low-temperature fixing properties. In addition, the toner base particles of the present embodiment have a porous structure and an appropriate volume median diameter, so that the number of contact points between toner particles is relatively small (the contact area between toner particles is relatively small). Therefore, the toner of the present embodiment can effectively suppress the aggregation of toner particles during heat-resistant storage, and has excellent heat-resistant storage properties. Furthermore, since the toner base particles contain a polyester resin, which is a resin having hydrolysis properties, they can be efficiently manufactured, for example, by the following method. First, toner raw material particles containing a polyester resin are prepared. Next, the toner raw material particles are subjected to a hydrolysis treatment to appropriately remove the polyester resin present on the surface of the toner raw material particles. As a result, a porous structure is formed in the toner raw material particles, and toner base particles having a porous structure are obtained. Note that, since the toner of the present embodiment contains a polyester resin, the low-temperature fixability is further optimized.
[0022] The toner of the present embodiment will be described in further detail below. Each of the components described below may be used alone or in combination of two or more, unless otherwise specified.
[0023] [Toner base particles] The toner base particles contain, for example, a binder resin as a main component. The toner base particles may further contain an internal additive (for example, at least one of a colorant, a release agent, a charge control agent, and a magnetic powder) as necessary. The toner base particles preferably further contain a colorant and a release agent as the internal additive.
[0024] (BET specific surface area) The BET specific surface area of the toner particles is 1.0 m 2 / g or more 1.4m 2 / g or less, 1.2m 2 / g or more 1.4m 2 The BET specific surface area of the toner base particles is preferably 1.0 m 2 By setting the BET specific surface area of the toner base particles to 1.4 m / g or more, the toner of the present embodiment can exhibit excellent low-temperature fixing property and heat-resistant storage stability. 2 By adjusting the molecular weight to be not more than 1 / g, the toner of the present embodiment can exhibit excellent heat-resistant storage stability.
[0025] (Volume Median Diameter (D 50 )) Volume median diameter of toner particles (D 50 ) is 6.0 μm or more and 8.0 μm or less, and preferably 6.0 μm or more and 6.5 μm or less, or 7.5 μm or more and 8.0 μm or less. In known toners in which the volume median diameter of the toner base particles is excessively small, the contact points between the toner particles increase due to the inclusion of fine toner particles (the contact area between the toner particles increases). As a result, the heat-resistant storage stability of known toners is reduced. In known toners in which the volume median diameter of the toner base particles is excessively large, the inclusion of coarse toner particles makes it difficult for the heat received from the fixing device during fixing to be transmitted to the entire toner image on the recording medium. As a result, the low-temperature fixability of known toners is reduced. In contrast, the toner of the present embodiment can exhibit excellent heat-resistant storage stability by making the volume median diameter of the toner base particles 6.0 μm or more. In known toners in which the volume median diameter of the toner base particles is 8.0 μm or more, the low-temperature fixability of known toners is reduced.
[0026] The volume median diameter of the toner particles is substantially the same as the volume median diameter of the toner base particles.
[0027] (Binding resin) The binder resin includes a polyester resin. The binder resin may further include a thermoplastic resin other than the polyester resin (hereinafter, may be referred to as other thermoplastic resin). Examples of the other thermoplastic resin include styrene resin, acrylic ester resin, olefin resin (e.g., polyethylene resin and polypropylene resin), vinyl resin (e.g., vinyl chloride resin, polyvinyl alcohol, vinyl ether resin, and N-vinyl resin), polyamide resin, and urethane resin. In addition, copolymers of these resins, that is, copolymers in which any repeating unit is introduced into the above resin (e.g., styrene-acrylic ester resin, and styrene-butadiene resin), can also be used as the other thermoplastic resin.
[0028] The content of the polyester resin in the binder resin is preferably 90% by mass or more, and more preferably 100% by mass. By making the content of the polyester resin in the binder resin 90% by mass or more, it becomes easier to introduce a porous structure into the toner base particles.
[0029] The content of the binder resin in the toner base particles is preferably 60% by mass or more and 90% by mass or less, and more preferably 70% by mass or more and 85% by mass or less. By setting the content of the binder resin in the toner base particles to 60% by mass or more and 90% by mass or less, it becomes easier to introduce a porous structure into the toner base particles.
[0030] Specifically, the toner base particles are obtained by, for example, performing a hydrolysis treatment on toner raw material particles containing a polyester resin. The hydrolysis treatment decomposes the polyester resin present on the surface of the toner raw material particles, and toner base particles having a porous structure are formed. If the toner raw material particles contain a relatively large amount of other components (e.g., colorant and release agent) other than the binder resin, the polyester resin is removed during the above-mentioned hydrolysis treatment, while the other components remain. As a result, an appropriate porous structure is reliably introduced into the toner base particles.
[0031] The polyester resin preferably contains an amorphous polyester resin and a crystalline polyester resin. Hereinafter, the polyester resin containing a crystalline polyester resin and an amorphous polyester resin may be simply referred to as a "mixed resin". When the toner base particles contain a mixed resin as a binder resin, it becomes easier to introduce a porous structure into the toner base particles, and the low-temperature fixability of the toner of this embodiment can be further optimized. In this case, the content of the amorphous polyester resin in the binder resin is preferably 80% by mass or more and 90% by mass or less. In addition, the content of the crystalline polyester resin in the binder resin is preferably 10% by mass or more and 20% by mass or less.
[0032] The polyester resin is obtained by polycondensation of one or more polyhydric alcohols and one or more polycarboxylic acids. Examples of the polyhydric alcohols for synthesizing the polyester resin include dihydric alcohols (e.g., diol compounds and bisphenol compounds) and trivalent or higher alcohols. Examples of the polycarboxylic acids for synthesizing the polyester resin include divalent carboxylic acids and trivalent or higher carboxylic acids. In place of the polycarboxylic acids, polycarboxylic acid derivatives capable of forming ester bonds by polycondensation (e.g., polycarboxylic acid anhydrides and polycarboxylic acid halides) may be used.
[0033] Examples of diol compounds include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 2-butene-1,4-diol, 1,5-pentanediol, 2-pentene-1,5-diol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, 1,4-benzenediol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0034] Examples of bisphenol compounds include bisphenol A, hydrogenated bisphenol A, ethylene oxide adducts of bisphenol A (e.g., polyoxyethylene(2,2)-2,2-bis(4-hydroxyphenyl)propane), and propylene oxide adducts of bisphenol A. In the ethylene oxide adducts of bisphenol A and the propylene oxide adducts of bisphenol A, the number of moles of ethylene oxide or propylene oxide added is preferably 1.0 mole or more and 5.0 moles or less, and more preferably 1.5 moles or more and 2.5 moles or less, respectively.
[0035] Examples of trihydric or higher alcohols include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, diglycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0036] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, cyclohexanedicarboxylic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, succinic acid, alkylsuccinic acids (more specifically, n-butylsuccinic acid, isobutylsuccinic acid, n-octylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid), and alkenylsuccinic acids (more specifically, n-butenylsuccinic acid, isobutenylsuccinic acid, n-octenylsuccinic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid).
[0037] Examples of trivalent or higher carboxylic acids include 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxylpropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, and empol trimer acid.
[0038] The polyester resin may further have a repeating unit derived from a vinyl compound, such as a styrene compound, (meth)acrylic acid, a (meth)acrylic acid alkyl ester, a (meth)acrylic acid phenyl ester, (meth)acrylonitrile, and vinyl chloride.
[0039] Examples of styrene compounds include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, pt-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene.
[0040] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, and lauryl (meth)acrylate.
[0041] As the polyhydric alcohol for synthesizing the amorphous polyester resin, a bisphenol A ethylene oxide adduct or a bisphenol A propylene oxide adduct is preferable.
[0042] As the polyvalent carboxylic acid for synthesizing the amorphous polyester resin, terephthalic acid or adipic acid is preferable.
[0043] As the amorphous polyester resin, a bisphenol A ethylene oxide adduct, a bisphenol A propylene oxide adduct, or a condensation polymer of terephthalic acid and adipic acid is preferable.
[0044] In the total repeating units contained in the above-mentioned condensation polymer, the content of repeating units derived from bisphenol A ethylene oxide adduct is preferably 50% by mass or more and 57% by mass or less. Similarly, the content of repeating units derived from bisphenol A propylene oxide adduct is preferably 14% by mass or more and 22% by mass or less. Similarly, the content of repeating units derived from terephthalic acid is preferably 14% by mass or more and 22% by mass or less. Similarly, the content of repeating units derived from adipic acid is preferably 7% by mass or more and 15% by mass or less.
[0045] As the polyhydric alcohol for synthesizing the crystalline polyester resin, ethylene glycol is preferred.
[0046] As the polyvalent carboxylic acid for synthesizing the crystalline polyester resin, sebacic acid is preferred.
[0047] The crystalline polyester resin preferably has a repeating unit derived from styrene and a repeating unit derived from butyl (meth)acrylate.
[0048] As the crystalline polyester resin, a copolymer of ethylene glycol, sebacic acid, styrene and butyl methacrylate is preferred.
[0049] In the total repeating units contained in the copolymer, the content of repeating units derived from ethylene glycol is preferably 7% by mass or more and 15% by mass or less. Similarly, the content of repeating units derived from sebacic acid is preferably 30% by mass or more and 38% by mass or less. Similarly, the content of repeating units derived from styrene is preferably 21% by mass or more and 29% by mass or less. Similarly, the content of repeating units derived from butyl methacrylate is preferably 27% by mass or more and 35% by mass or less.
[0050] (Coloring agent) The toner base particles preferably contain a colorant. As the colorant, a known pigment or dye can be used according to the color of the toner of the present embodiment. From the viewpoint of forming a high-quality image using the toner of the present embodiment, the content of the colorant is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 7 parts by mass or more and 12 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0051] The toner base particles may contain a black colorant. An example of the black colorant is carbon black. The black colorant may be a colorant toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.
[0052] The toner base particles may contain color colorants, including yellow colorants, magenta colorants, and cyan colorants.
[0053] (Release agent) The toner base particles preferably contain a release agent. The release agent is used, for example, for the purpose of imparting offset resistance to the toner of the present embodiment. From the viewpoint of imparting sufficient offset resistance to the toner of the present embodiment, the content of the release agent is preferably 3 parts by mass or more and 20 parts by mass or less, more preferably 7 parts by mass or more and 12 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0054] Examples of the release agent include aliphatic hydrocarbon waxes, oxides of aliphatic hydrocarbon waxes, vegetable waxes, animal waxes, mineral waxes, ester waxes mainly composed of fatty acid esters, and waxes in which a part or all of the fatty acid esters are deoxidized. Examples of the aliphatic hydrocarbon waxes include low molecular weight polyethylene, low molecular weight polypropylene, polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of the vegetable waxes include candelilla wax, carnauba wax, Japan wax, jojoba wax, and rice wax. Examples of the animal waxes include beeswax, lanolin, and spermaceti. Examples of the mineral waxes include ozokerite, ceresin, and petrolatum. Examples of the ester waxes mainly composed of fatty acid esters include montan acid ester wax and castor wax. An example of the wax in which the fatty acid ester is partially or completely deoxidized is deoxidized carnauba wax. As the release agent, an ester wax is preferable.
[0055] When the toner base particles contain a release agent, a compatibilizer may be added to the toner base particles in order to improve the compatibility between the binder resin and the release agent.
[0056] (Charge control agent) The toner base particles may contain a charge control agent. The charge control agent is used, for example, for the purpose of imparting excellent charge stability or excellent charge rise characteristics to the toner of the present embodiment. The charge rise characteristics of the toner of the present embodiment are an index of whether the toner of the present embodiment can be charged to a predetermined charge level in a short period of time. By incorporating a positively chargeable charge control agent in the toner base particles, the cationic nature of the toner base particles can be strengthened.
[0057] [External additives] The external additive adheres to the surface of the toner base particles. As the external additive, silica particles are preferred, and silica particles that have been subjected to a surface treatment to impart positive charging properties are more preferred. The number-average primary particle diameter of the silica particles is preferably 20 nm or more and 300 nm or less, more preferably 20 nm or more and 100 nm or less, and even more preferably 20 nm or more and 40 nm or less. By making the number-average primary particle diameter of the silica particles 20 nm or more, it is possible to suppress embedding of the silica particles in the toner base particles. In addition, by making the number-average primary particle diameter of the silica particles 300 nm or less, it is possible to suppress detachment from the toner base particles.
[0058] From the viewpoint of fully exerting the function of the silica particles while suppressing detachment from the toner base particles, the content of the silica particles in the toner particles is preferably 0.1 parts by mass or more and 15.0 parts by mass or less, and more preferably 0.5 parts by mass or more and 2.0 parts by mass or less, per 100.0 parts by mass of the toner base particles.
[0059] (Other external additive particles) The external additive may further contain other external additive particles other than silica particles. Examples of the other external additive particles include particles of metal oxides (specifically, alumina, magnesium oxide, zinc oxide, etc.), particles of organic acid compounds such as fatty acid metal salts (specifically, zinc stearate, etc.), and resin particles.
[0060] <Second embodiment: Toner manufacturing method> The second embodiment of the present invention relates to a method for producing a toner. The method for producing a toner of this embodiment is the same as the method for producing a toner of the first embodiment, and includes a dispersion preparation step of preparing a dispersion containing toner raw material particles, and a porosity forming step of obtaining toner base particles by forming a porous structure in the toner raw material particles. The toner raw material particles contain a polyester resin. In the porosity forming step, the dispersion is treated with a base to hydrolyze a part of the polyester resin present on the surface of the toner raw material particles. The method for producing a toner of this embodiment can efficiently produce the toner of the first embodiment.
[0061] The toner manufacturing method of the present embodiment preferably further includes a toner raw material particle preparation step of preparing toner raw material particles, and an external addition step of adhering an external additive to the surface of the toner base particles. In the present embodiment, the toner particles, the toner base particles, and the external additive are the same as those described in the first embodiment, and therefore the duplicated description will be omitted.
[0062] (Toner raw material particle preparation process) In this step, toner raw material particles are prepared by, for example, an aggregation method or a pulverization method. The toner raw material particles contain a polyester resin. The toner raw material particles preferably further contain the internal additive described in the first embodiment. The volume median diameter of the toner raw material particles can be the same as the volume median diameter of the toner base particles described in the first embodiment.
[0063] The aggregation method includes, for example, an aggregation step and a coalescence step. In the aggregation step, fine particles containing a polyester resin and an internal additive used as necessary are aggregated in an aqueous medium to form aggregated particles. In the coalescence step, components contained in the aggregated particles are coalesced in the aqueous medium to form toner raw material particles.
[0064] Next, the pulverization method will be described. The pulverization method allows toner raw particles to be prepared relatively easily and also allows for reduction in manufacturing costs. When toner raw particles are prepared by the pulverization method, the toner raw particle preparation process includes, for example, a melt-kneading process and a pulverization process. The toner raw particle preparation process may further include a mixing process before the melt-kneading process. In addition, the toner raw particle preparation process may further include at least one of a fine pulverization process and a classification process after the pulverization process.
[0065] In the mixing step, the polyester resin is mixed with an internal additive used as required to obtain a mixture. In the melt-kneading step, the materials (for example, the above-mentioned mixture) are melted and kneaded to obtain a melt-kneaded product. In the pulverizing step, the obtained melt-kneaded product is cooled, for example, to room temperature (25°C), and then pulverized to obtain a pulverized product. If it is necessary to reduce the diameter of the pulverized product obtained in the pulverizing step, a step of further pulverizing the pulverized product (fine pulverizing step) may be performed. In addition, if the particle size of the pulverized product is to be uniform, a step of classifying the obtained pulverized product (classifying step) may be performed. Through the above steps, the pulverized product, that is, the toner raw material particles, is obtained.
[0066] (Dispersion liquid preparation process) In this step, the toner raw particles are dispersed in an aqueous medium to prepare a dispersion liquid containing the toner raw particles. The content of the toner raw particles in the dispersion liquid is preferably 10% by mass or more and 40% by mass or less. As a method for dispersing the toner raw particles in an aqueous medium, for example, a method of stirring using a mixer can be mentioned.
[0067] (Porous process) In this process, the dispersion liquid is treated with a base (e.g., sodium hydroxide and potassium hydroxide) to hydrolyze a part of the polyester resin present on the surface of the toner raw material particles. This removes the polyester resin present on the surface of the toner raw material particles, and a porous structure is formed to obtain toner mother particles. In this process, the pH of the dispersion liquid is preferably 9 or more and 11 or less. That is, in this process, it is preferable to add an amount of base such that the pH of the dispersion liquid falls within the above-mentioned numerical range.
[0068] In this step, the treatment time with the base is preferably from 0.8 to 4.5 hours, more preferably from 3.5 to 4.5 hours, and the treatment temperature with the base is preferably from 30 to 50° C., more preferably from 37 to 43° C. By setting such conditions, an appropriate porous structure can be introduced into the toner raw material particles.
[0069] The toner base particles obtained in this step may be further subjected to a washing treatment with ion-exchanged water or the like and a drying treatment, if necessary.
[0070] (External addition process) In this process, toner particles are obtained by adhering an external additive to the surface of the toner base particles. The method for adhering the external additive to the surface of the toner base particles is not particularly limited, but may be, for example, a method in which the toner base particles and the external additive are stirred with a mixer or the like. EXAMPLES
[0071] The present invention will be described in more detail below using examples, but the present invention is not limited to the scope of the examples.
[0072] (Synthesis of amorphous polyester resin) Into a reaction vessel, 150 g of bisphenol A ethylene oxide adduct (average number of moles of ethylene oxide added: 2 moles), 50 g of bisphenol A propylene oxide adduct (average number of moles of propylene oxide added: 2 moles), 50 g of terephthalic acid, 30 g of adipic acid, and 54 g of tin(II) 2-ethylhexanoate were charged. Next, after the inside of the reaction vessel was filled with nitrogen, the reaction vessel was heated while stirring the contents of the reaction vessel until the temperature of the contents of the reaction vessel reached 235°C.
[0073] Next, the reaction vessel contents were subjected to a condensation polymerization reaction by stirring the reaction vessel contents while maintaining the inside of the reaction vessel in a nitrogen atmosphere and maintaining the temperature of the reaction vessel contents at 235°C. The condensation polymerization reaction was carried out until all of the resin raw materials (bisphenol A ethylene oxide adduct, bisphenol A propylene oxide adduct, terephthalic acid, and adipic acid) were dissolved. Next, the reaction vessel was depressurized until the pressure in the reaction vessel was 8.0 kPa. Next, while maintaining the pressure in the reaction vessel at 8.0 kPa and the temperature of the reaction vessel contents at 235°C, the reaction vessel contents were reacted until the physical properties of the reaction product (polyester resin) reached a predetermined value. This resulted in the production of an amorphous polyester resin. The amorphous polyester resin was determined to be amorphous because no clear endothermic peak was observed in the endothermic curve measured using a differential scanning calorimeter.
[0074] (Synthesis of crystalline polyester resin) In the synthesis of the crystalline polyester resin, a 1L four-neck flask equipped with a thermometer, a nitrogen inlet tube, a stirring device (stainless steel stirring blade), and a downflow condenser was used as a reaction vessel. 69.0 g of ethylene glycol, 214.0 g of sebacic acid, and 54.0 g of tin(II) 2-ethylhexanoate were charged into the reaction vessel. The reaction vessel was then set on a mantle heater. Nitrogen gas was then introduced into the reaction vessel through the nitrogen inlet tube, creating a nitrogen atmosphere (inert atmosphere) inside the reaction vessel. The temperature was then raised to 235°C over 2 hours while stirring the contents in the nitrogen atmosphere. After the temperature was raised, the contents were reacted (condensation polymerization reaction) while stirring under the conditions of a nitrogen atmosphere and a temperature of 235°C until the reaction rate reached 95% by mass or more. The reaction rate was calculated according to the formula "reaction rate = 100 x actual amount of water produced by reaction / theoretical amount of water produced".
[0075] After the reaction, the contents of the reaction vessel were cooled to 160°C, and a mixture of 156.0g of styrene, 195.0g of n-butyl methacrylate, and 0.5g of di-tert-butyl peroxide was dropped into the reaction vessel at a constant rate over 1 hour. After the dropwise addition, the contents were stirred for another 30 minutes while maintaining the temperature of the contents at 160°C (aging). After aging, the temperature and pressure in the reaction vessel were raised and reduced, and the contents were reacted for 1 hour under conditions of a reduced pressure atmosphere (pressure 8kPa) and a temperature of 200°C. After the reaction, the contents of the reaction vessel were cooled to 180°C. After cooling, the pressure in the reaction vessel was returned to normal pressure, and a radical polymerization inhibitor (4-tert-butylcatechol) was added to the reaction vessel. After that, the contents were heated to a temperature of 210°C over 2 hours at a constant rate, and then reacted at a temperature of 210°C for 1 hour. After the reaction, the pressure inside the reaction vessel was reduced, and the contents were reacted for an additional 2 hours under conditions of a reduced pressure atmosphere (pressure 40 kPa) and a temperature of 210° C. As a result, a crystalline polyester resin was obtained.
[0076] [Preparation of toner raw material particles] Using an FM mixer ("FM-20B" manufactured by Nippon Coke and Engineering Co., Ltd.), 70 parts by mass of the above-mentioned amorphous polyester resin, 12 parts by mass of the above-mentioned crystalline polyester resin, 9 parts by mass of a release agent ("Nissan Electol (registered trademark) WEP-8" manufactured by NOF Corporation, an ester wax), and 9 parts by mass of carbon black ("MA100" manufactured by Mitsubishi Chemical Corporation) were mixed at a rotation speed of 2400 rpm / min for 180 seconds.
[0077] The obtained mixture was melt-kneaded using a twin-screw extruder (Toshiba Machine Co., Ltd., "PCM-30") under the conditions of a material supply rate of 100 g / min, a shaft rotation speed of 150 rpm, and a set temperature (cylinder temperature) of 100°C. The obtained kneaded product was cooled. The cooled kneaded product was coarsely pulverized using a pulverizer (Hosokawa Micron Corporation, "Rotoplex (registered trademark) 16 / 8 type") under the condition of a set particle size of 2 mm. The obtained coarsely pulverized product was finely pulverized using a pulverizer (Freund Turbo Corporation, "Turbo Mill RS type") to obtain a finely pulverized product. The finely pulverized product was classified using a classifier (Nitetsu Mining Co., Ltd., "Elbow Jet EJ-LABO type"). As a result, the volume median diameter (D 50) Toner raw material particles (A) having a diameter of 5.9 μm were obtained. The volume median diameter was measured using a particle size meter ("Coulter Counter Multisizer 3" manufactured by Beckman Coulter, Inc.).
[0078] Toner raw particles (B) to (H) shown in Table 1 below were prepared in the same manner as in the preparation of toner raw particles (A), except that the coarse pulverization conditions, fine pulverization conditions, and classification conditions were appropriately changed. In the preparation of toner raw particles (E) to (H), the coarse pulverization conditions, fine pulverization conditions, and classification conditions were set so as to broaden the particle size distribution.
[0079] [Table 1]
[0080] [Toner Preparation] The toners of Examples 1 to 4 and Comparative Examples 1 to 12 shown in Table 2 below were prepared by the following methods.
[0081] [Example 1] (Dispersion liquid preparation process) Into a container of a mixer (PRIMIX Corporation's "Hibismix (registered trademark) 2P-1 type"), 100 parts by mass of water, 20 parts by mass of toner raw material particles (B), and 5 parts by mass of sodium lauryl sulfate were added. The speed of the mixer was set to a rotation speed of 20 rpm and a revolution speed of 20 rpm, and the contents of the container were stirred for 1 hour. As a result, a dispersion liquid containing the toner raw material particles (B) was obtained.
[0082] (Porous process) While continuing to stir the above-mentioned dispersion liquid using a mixer, the temperature of the dispersion liquid was raised to 40°C. Next, an aqueous NaOH solution was added dropwise to the dispersion liquid to adjust the pH of the dispersion liquid to 10. Next, while maintaining the temperature of the dispersion liquid at 40°C, the dispersion liquid was stirred for 3.0 hours (hereinafter, this stirring time may be referred to as the treatment time). As a result, the polyester resin (crystalline polyester resin and amorphous polyester resin) present on the surface of the toner raw material particles (B) was partially hydrolyzed to form a porous structure. As a result, the toner base particles (D50 Next, the dispersion was cooled to 25°C.
[0083] (Cleaning process) The wet cake-like toner base particles were collected from the cooled dispersion by filtration using a Buchner funnel. Next, a redispersion process in which the wet cake-like toner base particles were redispersed in ion-exchanged water and a filtration process in which the dispersion obtained by the redispersion process was filtered using a Buchner funnel to recollect the wet cake-like toner base particles were repeated five times in total. This resulted in the production of washed toner base particles.
[0084] (drying process) The wet cake of the washed toner base particles was supplied to a continuous surface modification device ("Coatmizer (registered trademark)" manufactured by Freund Corporation). This allowed the washed toner base particles to be dried, yielding dry toner base particles. The drying conditions for the Coatmizer (registered trademark) were a hot air temperature of 45°C and a blower air volume of 2 m. 3 / min.
[0085] (Measurement of specific surface area) The BET specific surface area of the toner base particles was measured by the BET method using nitrogen adsorption in accordance with "JIS (Japanese Industrial Standards) Z8830:2001 Measurement method for specific surface area of powder (solid) by gas adsorption". For the measurement, a fully automatic BET specific surface area measuring device ("Macsorb (registered trademark) HM MODEL-1208" manufactured by Mountec Co., Ltd.) was used. The measurement results are shown in Table 2 below.
[0086] (External addition process) Using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.), 100 parts by mass of the toner base particles after drying described above and 1 part by mass of silica particles ("AEROSIL (registered trademark) REA90" manufactured by Nippon Aerosil Co., Ltd., silica particles to which positive charging has been imparted by a surface treatment agent, number average primary particle diameter 20 nm) were mixed at a rotation speed of 3,500 rpm for 5 minutes. The resulting mixture was sieved through a 200 mesh (75 μm opening) sieve. As a result, the toner of Example 1 was obtained.
[0087] [Examples 2 to 4 and Comparative Examples 1 to 12] The toners of Examples 2 to 4 and Comparative Examples 1 to 8 were produced in the same manner as the toner of Example 1, except that the type of toner raw particles and the processing time in the porosity-making step were changed as shown in Table 2 below. The toners of Comparative Examples 9 to 12 were produced in the same manner as the toner of Example 1, except that the type of toner raw particles was changed as shown in Table 2 below and the porosity-making step was not performed. In the production of the toners of Comparative Examples 9 to 12, the dispersion obtained in the dispersion preparation step was directly subjected to the washing step without any processing.
[0088] [Table 2]
[0089] <Evaluation> The low-temperature fixability and heat-resistant storage stability were evaluated by the following methods for the toners of Examples 1 to 4 and Comparative Examples 1 to 12. The evaluation results are shown in Table 3 below.
[0090] [Low temperature fixability] For the evaluation of low-temperature fixing ability, a printer equipped with a roller-roller type heat and pressure fixing device (a modified version of Kyocera Document Solutions Inc.'s "FS-C5250DN" that allows the fixing temperature to be changed, nip width 8 mm) was used as the evaluation machine.
[0091] 100 parts by mass of a developer carrier (carrier for the printer "FS-C5250DN" manufactured by Kyocera Document Solutions Inc.) and 10 parts by mass of a toner used as a sample (specifically, any of the toners of Examples 1 to 4 and Comparative Examples 1 to 12) were stirred for 30 minutes using a bowl mill. As a result, a developer for evaluation (two-component developer) was obtained. The developer for evaluation (developer containing any of the toners of Examples 1 to 4 and Comparative Examples 1 to 12) was placed in the black developing device of the evaluation machine, and a refill toner (the same toner as that contained in the developer for evaluation) was placed in the black toner container of the evaluation machine.
[0092] Using an evaluation machine, under normal temperature and humidity conditions (temperature 20°C, humidity 50% RH), A4 size plain paper (basis weight 90g / m 2 ) with a linear velocity of 200 mm / sec and a toner loading of 1.0 mg / cm 2 A solid image (specifically, an unfixed toner image) was formed under the conditions above.
[0093] Next, the plain paper (evaluation paper) on which the solid image was formed was passed through the fixing device of the evaluation machine. At this time, the fixing temperature of the fixing device of the evaluation machine (specifically, the temperature of the fixing roller included in the fixing device of the evaluation machine) was set to 100°C or higher and 200°C or lower. Specifically, the fixing temperature was increased by 2°C from 100°C and fixing was performed at each temperature, and the minimum temperature (minimum fixing temperature) at which the solid image could be fixed on the evaluation paper was measured. Whether or not the solid image could be fixed on the evaluation paper was determined by the following folding and rubbing test.
[0094] In the folding and rubbing test, the evaluation paper that had been passed through the fixing device was folded so that the surface on which the solid image was formed was on the inside. More specifically, the evaluation paper was folded so that the folding line passed through approximately the center of the solid image. The folded evaluation paper was rubbed back and forth five times on the fold using a 1 kg weight covered with fabric without applying force from above (load 1 kg). Thereafter, the evaluation paper was unfolded, and the length of peeling of the toner in the folded part of the evaluation paper where the solid image was fixed (peeling length) was measured. If the peeling length was 1 mm or less, it was determined that the unfixed toner image had been fixed.
[0095] The low-temperature fixing property of a toner can be evaluated as "good (A)" when the minimum fixing temperature is 130°C or lower, and as "poor (B)" when the minimum fixing temperature is higher than 130°C.
[0096] [Heat-resistant storage stability] 3 g of toner (specifically, any of the toners of Examples 1 to 4 and Comparative Examples 1 to 12) was placed in a plastic container with a capacity of 20 mL and sealed. Next, the plastic container was tapped for 5 minutes. Next, the plastic container was left to stand in a thermostatic chamber set at 55° C. for 8 hours (heat treatment). After the heat treatment, the toner was taken out of the plastic container to obtain a toner for evaluating heat-resistant storage stability. The toner for evaluating heat-resistant storage stability was sieved using a powder property evaluation device ("Powder Tester (registered trademark)" manufactured by Hosokawa Micron Corporation) equipped with a 300 mesh (48 μm opening) sieve under the conditions of a rheostat scale of "5" and a time of 30 seconds. After sieving, the mass of the toner remaining on the sieve was measured. The degree of aggregation (unit: %) was calculated from the mass of the toner before sieving and the mass of the toner remaining on the sieve after sieving according to the formula: "degree of aggregation (%) = 100 x mass of toner remaining on the sieve / mass of toner before sieving." The heat-resistant storage stability was evaluated according to the following criteria.
[0097] (Standards for heat resistance storage) Good (A): The degree of aggregation is less than 20%. Poor (A): The degree of cohesion is 20% or more.
[0098] [Table 3]
[0099] The toners of Examples 1 to 4 contained toner particles. The toner particles were provided with toner base particles. The toner base particles contained a binder resin. The binder resin contained a polyester resin. The toner base particles had a porous structure. The volume median diameter of the toner base particles was 6.0 μm or more and 8.0 μm or less. The BET specific surface area of the toner base particles was 1.1 m 2 / g or more 1.4m 2 / g or less. The toners of Examples 1 to 4 were excellent in low-temperature fixability and heat-resistant storage stability.
[0100] On the other hand, the toners of Comparative Examples 1 and 2 had a volume median diameter of the toner base particles of less than 6.0 μm. It is considered that the toners of Comparative Examples 1 and 2 contained toner particles with an excessively small size, which resulted in a large number of contact points between the toner particles, and therefore an increased contact area. As a result, the toners of Comparative Examples 1 and 2 had poor heat-resistant storage stability.
[0101] The toners of Comparative Examples 3 and 4 had a volume median diameter of the toner base particles exceeding 7.9 μm. It is determined that the toners of Comparative Examples 3 and 4 contained toner particles with an excessively large size. Excessively large toner particles prevent the heat received from the fixing device during fixing from being transmitted to the entire toner image on the recording medium. As a result, the toners of Comparative Examples 3 and 4 had poor low-temperature fixing properties.
[0102] The toners of Comparative Examples 5 and 7 have a BET specific surface area of 1.4 m 2 / g. It is considered that the toner including toner base particles with an excessively large BET specific surface area has an increased contact area between toner particles. As a result, the toners of Comparative Examples 5 and 7 had poor heat-resistant storage stability.
[0103] The toners of Comparative Examples 6 and 8 have a BET specific surface area of 1.1 m 2 / g. It is considered that a toner containing toner base particles with an excessively small BET specific surface area cannot efficiently receive heat from a fixing device during fixing. As a result, the toners of Comparative Examples 6 and 8 had poor low-temperature fixing properties.
[0104] The toner base particles of the toners of Comparative Examples 9 and 10 did not have a porous structure. The toner base particles of the toners of Comparative Examples 9 and 10 had a large particle size distribution, and toner particles of excessively small size were also mixed in. It is therefore considered that the toners of Comparative Examples 9 and 10 had many contact points between toner particles, and the contact area was increased. As a result, the toners of Comparative Examples 9 and 10 had similar volume median diameters and BET specific surface areas of the toner base particles compared to the toners of Examples 1 and 2, but had poor heat-resistant storage stability.
[0105] The toner particles of Comparative Examples 11 and 12 did not have a porous structure. The toner particles of Comparative Examples 11 and 12 had a large particle size distribution, and contained toner particles of excessively large size. Excessively large toner particles inhibit the heat received from the fixing device during fixing from being transmitted to the entire toner image on the recording medium. As a result, the toners of Comparative Examples 11 and 12 had poor low-temperature fixing properties. [Industrial Applicability]
[0106] The toner and the method for producing the toner according to the present invention can provide a toner that can be used to form an image in, for example, a copier, a printer, or a multifunction machine. [Explanation of symbols]
[0107] 1 Toner particles 2. Toner base particles 3. External additives P Porous
Claims
1. A toner comprising toner particles, The toner particles include toner base particles, The toner base particles contain a binder resin, The binder resin includes a polyester resin, The toner base particles have a porous structure, The volume median diameter of the toner base particles is 6.0 μm or more and 8.0 μm or less, The BET specific surface area of the toner base particles is 1.1 m 2 / g or more 1.4m 2 / g or less.
2. The toner according to claim 1 , wherein the polyester resin comprises an amorphous polyester resin and a crystalline polyester resin.
3. The content of the amorphous polyester resin in the binder resin is 80% by mass or more and 90% by mass or less, The toner according to claim 2 , wherein the content of the crystalline polyester resin in the binder resin is from 10% by mass to 20% by mass.
4. The toner according to claim 1 , wherein the content of the binder resin in the toner base particles is 70% by mass or more and 85% by mass or less.
5. The toner according to claim 1 , wherein the toner particles further comprise an external additive attached to the surface of the toner base particle.
6. The toner base particles further contain a release agent, 3. The toner according to claim 1, wherein the content of the release agent is 7 parts by mass or more and 12 parts by mass or less with respect to 100 parts by mass of the binder resin.
7. A method for producing the toner according to claim 1 or 2, comprising the steps of: a dispersion liquid preparation step of preparing a dispersion liquid containing toner raw material particles; a porosity forming step of forming the porous structure in the toner raw material particles to obtain the toner base particles; Inclusive of the toner raw material particles contain the polyester resin, In the porosity-forming step, the dispersion is treated with a base to hydrolyze a part of the polyester resin present on the surface of the toner raw material particles.
8. The method for producing a toner according to claim 7 , wherein in the porosity forming step, the pH of the dispersion liquid is 9 or more and 11 or less.
9. In the porosity forming step, The treatment time with the base is 0.8 hours or more and 4.5 hours or less, The method for producing a toner according to claim 7 , wherein the temperature for the treatment with the base is 30° C. or more and 50° C. or less.
Citation Information
Patent Citations
Capsule toner, method for manufacturing the same and two component developer including capsule toner
JP2022145063A
Cited By
Propulsion system for vessel
EP4813829A1